The association between supportive social ties and autonomic nervous system function: differences between family ties and friendship ties in a cohort of older adults - Bosle, Catherin; Brenner, Hermann; Fischer, Joachim E.; Jarczok, Marc N.; Schöttker, Ben; Perna, Laura; Hoffmann, Kristina; Herr, Raphael (European journal of ageing, 2022)
Supportive family and friendship ties can serve different functions and thus might show different associations with an individual’s health. Particularly, older adults might show varying health benefits of different types of supportive ties depending on their marital and retirement status. Our aim is to analyze relationships between different types of supportive social ties and autonomic nervous system (ANS) function, a physiological indicator of health that can help to establish the biological plausibility of the association—measured by heart rate variability (HRV). We present cross-sectional linear regression analyses of a German cohort of community-dwelling older adults (2008-2010; n = 1,548; mean age = 68.7 years). Our findings indicate that supportive friendship ties show significant positive associations (i.e., higher HRV) in individuals that are either not married or above retirement age. Supportive family ties show significant positive associations in individuals below retirement age. Significant results vanish or are reduced after accounting for behavioral/physical and psychological/cognitive indicators. We conclude that programs supporting the development or maintenance of friendship ties might be especially beneficial in unmarried older adults and adults above retirement age.